(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Coronaviruses are a broad strain that includes a group of viruses which may cause a respiratory diseases ranging in severity from common colds to more severe diseases that lead to death. Recently in China, the emerging disease Covid-19 was discovered, which causes a range of symptoms such as fever, dry cough, fatigue, aches and pains, headaches, nasal congestion and loss of taste or smell. The new Corona disease (COVID-19) has forced the entire world to face one of the most difficult challenges in contemporary history, as this virus has infected millions and killed hundreds of thousands of people in various age groups. It is a grave mistake to describe this challenge as a health crisis only. It is a pandemic large-scale humanitarian crisis that is leading to the misery and suffering of all humankind and pushing its social and economic well-being to the brink of collapse